2016
DOI: 10.1002/chem.201604107
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Analysis of Self‐Assembled PEGylated Hexaphenylalanine Photoluminescent Nanostructures

Abstract: Despite the growing literature about diphenylalanine-based peptide materials, it still remains a challenge to delineate the theoretical insight into peptide nanostructure formation and the structural features that could permit materials with enhanced properties to be engineered. Herein, we report the synthesis of a novel peptide building block composed of six phenylalanine residues and eight PEG units, PEG -F6. This aromatic peptide self-assembles in water in stable and well-ordered nanostructures with optoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
84
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(96 citation statements)
references
References 64 publications
10
84
2
Order By: Relevance
“…Owing to the close relationship between the optoelectronic properties and the structural motif in these systems, PL is currently used as a promising probe to detect the formation of amyloid fibrils. We demonstrated that empty PEG 8 ‐F6‐based NSs, at a concentration of 10 mg mL −1 , are able to emit at 460 nm (Figure S3 in the Supporting Information) . At this very high concentration it was possible to detect a broad peak between 370 and 410 nm in the UV/Vis spectrum (Figure S4 in the Supporting Information), partially affected by the tail of the main absorbance peak centered at 257 nm, which is typical for the phenyl ring.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Owing to the close relationship between the optoelectronic properties and the structural motif in these systems, PL is currently used as a promising probe to detect the formation of amyloid fibrils. We demonstrated that empty PEG 8 ‐F6‐based NSs, at a concentration of 10 mg mL −1 , are able to emit at 460 nm (Figure S3 in the Supporting Information) . At this very high concentration it was possible to detect a broad peak between 370 and 410 nm in the UV/Vis spectrum (Figure S4 in the Supporting Information), partially affected by the tail of the main absorbance peak centered at 257 nm, which is typical for the phenyl ring.…”
Section: Resultsmentioning
confidence: 85%
“…Recently, several authors reported a surprising PL phenomenon for fibrillary networks such as amyloid fibrils and for peptide‐based NSs, both of them characterized by a high content of cross‐β structures . These systems show a fluorescence emission peak at 460 nm when excited at 370 or at 410 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to well‐known biomaterials' counterparts applied in implantable photonics, for instance, silk fibers, polymers, hydrogels, and more, these peptide‐based nanostructures have significantly higher refractive index ≈1.6 providing strong optical confinement of peptide optical waveguides . Another key functional optical effect is a new phenomenon of intrinsic tunable visible fluorescence (FL) recently revealed in different bioinspired peptide nanostructures …”
Section: Introductionmentioning
confidence: 99%